(untitled) (Research, Society and Development, 2021)
Agricultural land use causes changes in physical and chemical attributes of the soil, due to the management practices employed the productive capacity of the soil can be compromised under different agricultural systems. The soils of Porto Alegre are quite diverse reflecting the geology, topography and drainage network of the region, and include lowland soils, like the alluvial plain of the Arroio Dilúvio. This study was carried out in four landscape units (Native Forest, Agroforestry System, Horse Farm and Agricultural Crops), to assess changes in soil characteristics after different types of land use and management on the plain of the Dilúvio Arroio. We sampled disturbed and undisturbed soil samples for chemical (pH, EC, V, SOM, CEC, Al3+, H+Al) and physical analysis (porosity, microporosity and macroporosity). These chemical and physical attributes of the soils, especially pH, V%, SOM, CEC and Al3+, underwent changes under the different types of land use and management, with significant differences. Most changes were detected in the cropland soils. Multivariate analysis demonstrated the influence of the different types of land use, at the surface, land use and management had the greatest influence, while at depth, the proximity of the areas was the predominant factor.